Development of plant systemic resistance by beneficial rhizobacteria: Recognition, initiation, elicitation and regulation - Zhu, Lin; Huang, Jiameng; Lu, Xiaoming; Zhou, Cheng (Frontiers in Plant Science, 2022)
A plant growing in nature is not an individual, but it holds an intricate community of plants and microbes with relatively stable partnerships. The microbial community has recently been demonstrated to be closely linked with plants since their earliest evolution, to help early land plants adapt to environmental threats. Mounting evidence has indicated that plants can release diverse kinds of signal molecules to attract beneficial bacteria for mediating the activities of their genetics and biochemistry. Several rhizobacterial strains can promote plant growth and enhance the ability of plants to withstand pathogenic attacks causing various diseases and loss in crop productivity. Beneficial rhizobacteria are generally called as plant growth-promoting rhizobacteria (PGPR) that induce systemic resistance (ISR) against pathogen infection. These ISR-eliciting microbes can mediate the morphological, physiological and molecular responses of plants. In the last decade, the mechanisms of microbial signals, plant receptors, and hormone signaling pathways involved in the process of plant ISR has been well investigated. In this review, plant recognition, microbial elicitors, and the related pathways during plant-microbe interactions are discussed, with highlights on the roles of root hair-specific syntaxins and small RNAs in the regulation of the PGPR-induced ISR in plants.